Anticipatory Suppression of Nonattended Locations in Visual Cortex Marks Target Location and Predicts Perception - Sylvester, Chad M. (Society for Neuroscience, 2008)
Spatial attention is associated with modulations in prestimulus, anticipatory blood oxygen level-dependent (BOLD) activity across the brain. It is unclear, however, if these anticipatory modulations depend on the computational demands of the upcoming task. Here, we show that anticipation of low-contrast stimuli, relative to high-contrast stimuli, is associated with increased prestimulus BOLD activity in the frontal eye field (FEF) and the posterior inferior frontal sulcus (IFS) but not in the intraparietal sulcus (IPS). In visual cortex, anticipation of low-contrast stimuli is associated with increased suppression of activity corresponding to unattended (but not attended) locations, and this suppression predicts whether subjects will accurately perceive low-contrast stimuli. These results suggest that when a stimulus will be difficult to distinguish from the background, top-down signals from FEF and IFS can facilitate perception by marking its location through the suppression of unattended locations in visual cortex.